The Impact of physical activity and screen time on mental, physical and social health in children and adolescents: a narrative review - Stępień, Dawid; Nawrocka, Natalia; Hojda, Alicja; Bednarek, Filip; Małajewicz, Izabela; Plinta, Olga; Pietrzyk, Małgorzata; Rodak, Hanna; Oskroba, Karolina (Journal of Education, Health and Sport, 2026)
Background: Digital technologies have become deeply embedded in the everyday lives of children and adolescents, while physical activity levels are declining in many countries. These parallel trends raise concerns about their impact on mental, physical and social health. Aim: The aim of this narrative review is to summarize current knowledge on the relationships between physical activity, different forms of screen use (including social media and problematic smartphone use) and health outcomes in youth. Results: Evidence from reviews and large observational studies indicates that high total screen time is associated with more depressive and anxiety symptoms, reduced wellbeing, sleep disturbances, obesity and school difficulties. Intensive social media use and problematic smartphone use show particularly strong links with depression, anxiety, loneliness and functional impairment, and may display addiction-like features. In contrast, regular physical activity is consistently related to better mental health, higher life satisfaction and healthier sleep patterns, and may partly buffer the negative effects of excessive screen exposure. Sleep, loneliness and family context appear as important mediators and moderators of these associations. Conclusions: Excessive screen time and problematic smartphone use represent modifiable risk factors for youth health, whereas physical activity is a central protective factor that supports healthy development. Prevention strategies should therefore focus on promoting regular movement, setting limits on evening and night-time screen use, supporting healthy sleep hygiene and encouraging balanced, purposeful use of digital media in families, schools and health care settings.